Women’s Islamic Shariah Compliant Dress: An Overview - Zaleha Arshad,; Asliza Aris,; Zainuddin Md. Nor,; Arasinah Kamis, (Advances in Humanities and Contemporary Studies, 2024)
Fashion and religion are often said to be interlinked because of the rise of modest dress trends for Muslim women. However, many Muslim women dress in Muslim trends not dictated by religious requirements; as a result, the Muslim clothes they wear do not match the standards for appropriate Muslim attire. The reason is clothing has a purpose for a Muslim in that it is a tool that may be used to hide “awrah”, which are areas of the body that should not be seen by anybody other than members of the same family in line with religious orders. In short, Muslims may only wear clothes that are according to the Islamic dress code, which is a Sharia rule that determines what forms of clothing are allowed (i.e., Halal) and prohibited (i.e., Haram). Increases in the media's portrayal of important persons dressed in Islamic clothing and the size of the market for Islamic apparel have helped to elevate Islamic clothing to the status of a major fashion trend. Modern forms of communication, especially the Internet and social networking sites, have helped bring Islamic feminism into the mainstream. Since modesty is a maqasid al-shari'ah, one might achieve it by covering awrah.